Challenges during the realization of an international research project on leishmaniasis in Colombia - Suschinel, Raluca; Jaimes-Mogollón, Aylen Lisset; Gutiérrez-Marín, Reinaldo; Peña-Cortés, Luís Carlos; Mendoza-Ibarra, Jesús Alberto; Flórez-Gélvez, José; Dumbravă, Cătălin; Uzunof, Marius; Simion, Violeta Elena; Ionescu, Radu (Frontiers in Public Health, 2023)
Leishmaniasis is an infectious disease that belongs to the top 10 neglected tropical diseases. It mainly affects the poor population from tropical and subtropical areas of the World, which lacks sufficient resources and means to fight against this disease. With this in mind, the European Commission has funded an international collaborative research project in which are participating various institutions from South America, North Africa and Europe. The main objective of this project is the development of a fast, less expensive, non-invasive and easy to use alternative method for leishmaniasis diagnosis in dogs, one of the main reservoirs of leishmaniasis spread to humans. In this perspective article, we present our personal insight and opinion regarding the challenges of realizing a joint international research project on leishmaniasis in Colombia, a country where leishmaniasis is endemic, as well as regarding the involvement of the Public Health institutions and the local population from this country.